Psychological resources to optimize training and resilience in resilience in disaster risk management - Cortés Trujillo, Engels Germán (2016)
The present article revolves around the problems and the alternatives of solution of the training of facilitators in the Management of the Risk of Disasters (DRM). Deep limitations of trainers are described in terms of technical and methodological bases, which has no impact on the generation of community resilience. This writing makes several proposals regarding the selection of the most appropriate tools in the training. The basis of all of them is neuropsychology. Thus, we recognize the importance of an interactive teaching method: the pedagogy of error, experiential training, learning based on emotions, practical ability (more than the theoretical term), multisensory stimulation, metacognition, among others. Finally, it is emphasized that these resources are meant to be only methodological proposals that must be adapted to the risks and the specific conditions of each community.